2005
DOI: 10.1051/0004-6361:20048124
|View full text |Cite
|
Sign up to set email alerts
|

The primordial binary population

Abstract: Abstract. We present the results of a near-infrared adaptive optics survey with the aim to detect close companions to Hipparcos members in the three subgroups of the nearby OB association Sco OB2: Upper Scorpius (US), Upper Centaurus Lupus (UCL) and Lower Centaurus Crux (LCC). We have targeted 199 A-type and late B-type stars in the K S band, and a subset also in the J and H band. We find 151 stellar components other than the target stars. A brightness criterion is used to separate these components into 77 bac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
263
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(300 citation statements)
references
References 57 publications
31
263
2
Order By: Relevance
“…The distribution function of mass ratios is generally described as a power law ( f (μ) ∝ μ γ ), but the value of γ is still much debated in the literature (Duquennoy & Mayor 1991;Shatsky & Tokovinin 2002;Kouwenhoven et al 2005) and therefore we will take it as a free parameter 1 . Figure 6 shows the evolution with time of the type Ia SN rate for different models and different SFRs, analogously to Fig.…”
Section: Type Ia Sn Ratesmentioning
confidence: 99%
“…The distribution function of mass ratios is generally described as a power law ( f (μ) ∝ μ γ ), but the value of γ is still much debated in the literature (Duquennoy & Mayor 1991;Shatsky & Tokovinin 2002;Kouwenhoven et al 2005) and therefore we will take it as a free parameter 1 . Figure 6 shows the evolution with time of the type Ia SN rate for different models and different SFRs, analogously to Fig.…”
Section: Type Ia Sn Ratesmentioning
confidence: 99%
“…Raghavan et al 2010;Janson et al 2012), but with a strong bias towards equal masses at small binary separations (De Rosa et al 2014). However, Kouwenhoven et al (2005) found that for a sample of young A-stars, the mass ratio is biased towards unequal masses, indicating that accretion at young ages plays an important role in changing the primordial mass ratio into the one observed in older systems. This is supported by simulations that find accretion occurs primarily onto the secondary (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…It is widely recognised that the majority of main sequence stars and pre-main sequence stars are in binary systems and that these binaries have various distributions in mass ratio q, binary separation, and binary frequency (Duquennoy & Mayor 1991;Ghez et al 1993;Kouwenhoven et al 2005;Raghavan et al 2010;Kraus et al 2011;De Rosa et al 2014). For main sequence stars, Duquennoy & Mayor (1991) provided statistics of G-dwarf binary systems.…”
Section: Introductionmentioning
confidence: 99%
“…For young stellar objects (YSOs), the number of binaries with intermediate mass YSOs decreases with increasing q (Kouwenhoven et al 2005). In contrast, the number of binaries with low-mass YSOs increases with increasing q (Kraus et al 2011), and have a log-normal separation distribution.…”
Section: Introductionmentioning
confidence: 99%